LanguageFold: A Bio-inspired Hierarchical Sparse Attention Mechanism for Large Language Models - Wu, Yunyi; Huang, Kai (LangTaoSha Preprint Server, 2026)
Large language models predominantly rely on the Transformer architecture, whose self-attention mechanism incurs a quadratic computational cost O(N2) with respect to input length, leading to significant memory and computation bottlenecks when processing ultra-long contexts. This work proposes LanguageFold, a hierarchical sparse attention mechanism inspired by the Self-Returning Random Walk model of genome folding (Huang et al. 2020). LanguageFold decomposes global attention into dynamically constructed tree attention with a theoretical scaling of O(NlogN). Preliminary experiments on prompt-based generation and the DROP reading comprehension benchmark indicate that this tree-structured attention enables efficient language processing while preserving accuracy and enhancing structural interpretability. These results highlight the promise of genome-inspired attention mechanisms for optimizing the scalability of large language models.